تصور مقترح لمؤسسات المعرفة کحاضنة للابداع باستخدام مدخل ادارة المواهب - د. أمینة خیر توفیق (المجلة الدولية لعلوم المكتبات والمعلومات)
Today, knowledge institutions must retain their valuable employees, whichare the most important and valuable assets, because it is difficult and expensiveto obtain an alternative with the same distinction in the competitive environment.Hence, the need for knowledge institutions today for Talent Management, andseeks to develop the skill set and provide the opportunity for employees toexpand their experience at work, while at the same time providing the talent tothe institution that needs them to grow and develop in the work.Therefore, the researcher saw the need to highlight Talent Management'sentrance and the importance of applying it to the knowledge institutions, due tothe impact it will have on the knowledge institutions that adopt this approach andits impact on its culture.The methodology of document analysis (the method of content analysis oroffice research as called by some methodological scientists) is based on theintellectual output, published on the subject of human talent management ingeneral, in addition to the field of researcher's experience and interviews with thestaff of some knowledge institutions, as well as through the knowledge of theresearcher of a number of employees of those institutions and those whoadminister them.